Students’ psychological problems in speaking: a case study on speaking II class of STKIP PGRI Banjarmasin - Ninuk Krismanti; Maria Margaretha Siregar (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This study is intended to describe psychological problems faced by the students taking Speaking II class at STKIP PGRI Banjarmasin. The researchers believe that in learning English, students do not only have linguistic problems but also psychological problems. This study is conducted under a case study design. The instruments used in this study are questionnaires and interviews. The technique of sampling applied in this study is total population technique of sampling. 34 students are chosen as the subjects of the study. Of five psychological problems identified, it is found that there are only four prominent problems faced by the students in speaking: (1) lack of confidence, (2) fear of mistakes, (3) shyness, and (4) anxiety. Most of the students do not have problem regarding their motivation.